A qualitative investigation of the origins of excessive work behaviour. Issue 2 (9th February 2018) - Kirrane, Melrona; Breen, Marianne; O'Connor, Cliódhna
Abstract : Studies of workers who engage in excessive work behaviour continue to attract the attention of researchers. Most research in this field adheres to quantitative methodologies aligned to the addiction or trait paradigms and largely focuses on correlates and consequences of such behaviour. However, within this literature, empirically based understandings of the factors that propel individuals to engage in excessive work patterns are sparse. Resting on socio‐cultural theories of work, we adopt a novel approach to this field of enquiry and examine the genesis of excessive working using a qualitative methodology. We use discourse analysis to comparatively explore data from a sample of twenty‐eight workers comprising excessive and non‐excessive workers. Our study identified the roles of family of origin, educational experience, and professional norms as clear drivers of excessive work patterns. Data to support the dominant addiction and trait paradigms within this research domain were equivocal. Lifestyle decision‐making differentiated the comparison group from the excessive workers. We discuss our findings with reference to theories of workaholism and consider their implications for the evolution of this field. Practitioner points: Organizational culture can strongly influence the emergence of excessive work patterns among employees. Human resource professionals and organizational leaders are in a position to intervene in the development and support of work cultures that are conducive to effective work patterns Employee selection and assessment procedures should be sufficiently in‐depth to gather relevant information into the personal backgrounds of applicants Employee development initiatives should take account of learned work orientations to ensure the effectiveness of interventions.